HILIC-MS/MS Analysis of Adenosine in Patient Blood - Christina Virgiliou; Nikolaos Fragakis; Melani Sotiriadou; Vassilios Vassilikos; Spiros Gerou; Georgios Theodoridis; Helen Gika (Separations, 2021)
Adenosine is a purine ribonucleoside with important roles in various physiological processes. A number of studies have indicated the importance of adenosine in cardiovascular diseases including syncope; however, the accurate determination of adenosine in human blood is challenging due to the molecule’s instability. In the present study, we report a simple method for the pre-treatment of blood samples and the development of a fast and efficient hydrophilic interaction chromatographic tandem mass spectrometry method for the analysis of adenosine in patient blood. During collection, samples were mixed directly with a solvent mixture containing 95% acetonitrile and 10 mM ammonium formate in a Vacutainer tube, resulting in successful prevention of adenosine metabolic processes and direct blood sample deproteinization. The method was validated according to bioanalytical industry guidelines and found to be accurate, repeatable, specific and sensitive with LLOQ 0.005 μg/mL, thus allowing its application in the analysis of real clinical samples.